2003
DOI: 10.1038/sj.leu.2402843
|View full text |Cite
|
Sign up to set email alerts
|

Fibrates and medroxyprogesterone acetate induce apoptosis of primary Burkitt's lymphoma cells and cell lines: potential for applying old drugs to a new disease

Abstract: Current therapies for Burkitt's lymphoma (BL) utilise combined cytotoxic chemotherapy, but these treatments are not always available in areas where the disease is endemic and are also markedly less successful in AIDS-related BL. Therefore, additional therapies are urgently required. We demonstrate here that combined fibrates and MPA exert powerful, antiproliferative actions against well-characterised Daudi, Raji and L3055 BL cell lines and primary BL cells. Detailed studies in L3055 demonstrated that this acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…5C). Our earlier observations demonstrated that AML cell killing by BaP requires a >96-hour exposure (9), whereas killing of eBL cells is more rapid (7). Consistent with this, oleate induced a strong antiapoptotic effect in the Burkitt cell lines, as measured by decreased Annexin V staining, which was not observed in AML cells (Fig.…”
Section: Bap Treatment Modifies the Expression Of Key Enzymes Involvesupporting
confidence: 67%
See 1 more Smart Citation
“…5C). Our earlier observations demonstrated that AML cell killing by BaP requires a >96-hour exposure (9), whereas killing of eBL cells is more rapid (7). Consistent with this, oleate induced a strong antiapoptotic effect in the Burkitt cell lines, as measured by decreased Annexin V staining, which was not observed in AML cells (Fig.…”
Section: Bap Treatment Modifies the Expression Of Key Enzymes Involvesupporting
confidence: 67%
“…This approach has already been successful in reducing mortality in hematologic malignancies (5,6). Using this method, we previously identified that the combination of the lipid lowering drug, bezafibrate, and the contraceptive, medroxyprogesterone acetate (MPA), has potent and cancer cell selective in vitro anticancer effects against AML, eBL, chronic lymphocytic leukemia, and B-cell non-Hodgkin lymphoma cells (7)(8)(9)(10). The potency of this combination (denoted BaP) extended to the clinic demonstrating efficacy with low toxicity in clinical trials in AML (trial registration number ISRCTN50635541; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Acting through diverse mechanisms, these compounds usually retard or inhibit progression through the cell cycle and induce apoptosis. Examples of such compounds include fibrates and medroxyprogesterone acetate in Burkitt's lymphoma cells, 1 and psychotropics in B-cell-derived lines. 2,3 Thalidomide, an antiemetic which was withdrawn from the market in the 1960s, is thought to act by inducing cell differentiation and thereby preventing unrestrained proliferation of immature myelogenous cells.…”
Section: Introductionmentioning
confidence: 99%
“…BEZ is a lipid-lowering agent that mediates its activity as a ligand of the nuclear receptor PPARa and MPA is an orally active contraceptive progestogen. The study was based on our previous experience in Burkitts lymphoma 9 and acute myeloid leukemia (AML) [10][11][12] (Khanim et al, 2008, unpublished data). We show that both BEZ and MPA induce apoptosis in primary CLL cells and that the combination BEZ þ MPA is significantly more proapoptotic than either agent alone.…”
Section: Introductionmentioning
confidence: 99%